Scaling social impact : new thinking - Bloom, Paul N.; Skloot, Edward (Social entrepreneurship, 2010)
Many social entrepreneurs struggle to take successful, innovative programs that address social problems a local or limited basis and scale them up to expand their impact in a more widespread, deeper, and efficient way.The editors address this issue with a comprehensive collection of original papers written by leading scholars